A neornithischian dinosaur from the Middle Jurassic Xintiangou Formation of Yunyang, Chongqing, China: the earliest record in Asia. (3rd July 2021) - Li, Ning; Dai, Hui; Tan, Chao; Hu, Xufeng; Wei, Zhaoying; Lin, Yu; Wei, Guangbiao; Li, Deliang; Meng, Li; Hao, Baoqiao; You, Hailu; Peng, Guangzhao
ABSTRACT: A new neornithischian dinosaur, Sanxiasaurus modaoxiensis gen. et sp. nov., is described based on a partial postcranial skeleton from the Middle Jurassic Xintiangou Formation of Yunyang, Chongqing Municipality, China. It is the first neornithischian dinosaur from the Middle Jurassic Xintiangou Formation of Sichuan Basin, and also the earliest record of a neornithischian dinosaur in Asia. It differs from other neornithischians in possessing the following unique combination of characters: at least four sacrals; humerus strongly bowed laterally along its length; obturator process located at mid-length of ischial shaft; lesser trochanter of femur broadened, wing shaped and subequal in anteroposterior width to greater trochanter; distal tibia with elongate posterolateral process. Phylogenetic analysis shows that Sanxiasaurus modaoxiensis is positioned near the base of neornithischia. This find extends the Asia neornithischian stratigraphic horizon to the lower Middle Jurassic.